Implications of Cyber Bullying, Depression, Anxiety and Stress on Student Academic Achievement - Karsodikromo, Yatiman; Husin, Mohd Razimi; Razali, Abdul Rahim (Journal of Humanities and Social Sciences (JHASS), 2022)
Kajian ini bertujuan mengenal pasti pengaruh buli siber, kemurungan, kebimbangan dan tekanan terhadap pencapaian akademik murid. Kajian kualitatif ini meneroka implikasi buli siber ke atas lima orang murid mangsa buli siber dan telah dikenal pasti mempunyai tahap kemurungan, kebimbangan dan tekanan yang sangat tinggi melalui ujian soal selidik. Dapatan yang diperolehi melalui analasis tema menunjukkan antara implikasi yang dihadapi seperti tekanan perasaan, mudah tersinggung, bertindak keterlaluan, kesedihan, menyalahkan diri, merasa tidak dihargai, kecewa dan putus harapan, keinginan membunuh diri, malu, gangguan perasaan, bimbang dan takut, memendam perasaan, kurang yakin diri, kemarahan, hilang semangat dan implikasi akademik seperti tidak fokus dan ponteng sekolah. Kesimpulanya, buli siber membawa implikasi kemurungan, kebimbangan dan tekanan dari aspek emosi, psikologi dan fizikal. Penemuan daripada kajian ini dapat digunakan oleh pihak pemegang taruh khususnya dalam bidang pendidikan bagi merangka plan tindakan pemulihan ke atas mangsa buli siber. Implications of Cyber Bullying, Depression, Anxiety and Stress on Student Academic Achievement Abstract: This study aims to identify the influence of cyber bullying, depression, anxiety and stress on student academic achievement. This qualitative study explored the implications of cyberbullying on five students who were victims of cyberbullying and were identified as having very high levels of depression, anxiety and stress through a questionnaire test. Findings obtained through theme analysis show among the implications faced such as emotional stress, irritability, overacting, sadness, self-blame, feeling unappreciated, disappointed and hopeless, suicidal desire, shame, emotional disturbance, worry and fear, harboring feelings, lack of self-confidence, anger, loss of enthusiasm and academic implications such as lack of focus and skipping school. In conclusion, cyber bullying has implications for depression, anxiety and stress from emotional, psychological and physical aspects. The findings from this study can be used by stakeholders, especially in the field of education, to formulate a recovery action plan for victims of cyber bullying. Keywords: Anxiety, Cyberbullying, Depression, Stress.